A Management in a New Era with a Pure Mind - Ratchusanti, Sirikiat; Kitthitinan, Phathranit; Seedapeng, Kusuma; Ratchusanti, Jermkhuan; Sattayopat, Panida; Inchai, Mathana; Saengkeaw, Sudarat; Tanratanakul, Siroch; Chansong, Suphanit (วารสารวิทยาการจัดการและการสื่อสาร, 2023)
This article focuses on studying documents, textbooks, and related research compiled into academic articles. The objective is to introduce the concepts of corporate governance and corporate social responsibility based on business ethics to transform traditional management into modern management. The study found that current and future business management must focus on corporate governance, which is transparent, fair, verifiable, and for the benefit of society. Business management is not just a matter of law enforcement. Nevertheless, it must focus on corporate social responsibility. Therefore, this will increase sales and market share, strengthen brand positioning, enhance corporate image and capability, increase the ability to attract, motivate, and retain personnel, reduce operating costs, and build confidence with investors. As a result, it leads to the sustainable success of the business.